REGIONAL ASSET MANAGEMENT MECHANISM OF WEST ACEH DISTRICT (SHARIA ASSET MANAGEMENT PERSPECTIVE ANALYSIS AND PERMENDAGRI NO. 19 YEAR 2016) - Husin, M (IHTIYATH : Jurnal Manajemen Keuangan Syariah, 2021)
This Study aims to describe the management of regional management in west Aceh regency and to determine whether or not the regional asset management is appropriate from the perspective of sharia asset management and PERMENDAGRI number 19 of 2016. the approach of this research is qualitative with descriptive analysis method. the sample used in this study is the civil servants of the West Aceh regional financial management agency (BPKD) who have a relationship whit regional asset management policies. the result of the study show that the management of fixed assets/regional property at the regional management agency (BPKD) Aceh Barat has done it optimally and in accordance with the systems and procedures of the cycle of managing the property of the region as stipulated in domestic regulation number 19 of 2016 concerning guidelines for the management of regional property. planning according to needs and procurement of asset carried out in a transparent manner as well as utilization that can be utilized by the community with a borrow and use system. the implementation of asset management is also in accordance with Islamic law, namely management which is based on Islamic values such as trust, reliability and freedom, balance and can be accounted for. these Islamic principles are applied and used as the basis for the asset management mechanism. some of the obstacles or inhibiting factors encounted in implementing the regional property management cycle are human resources due to the need for specific knowledge and understanding of the regional-owned asset management mechanism.